2015
DOI: 10.1039/c4cp04853a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repulsive interaction on the electric double layer of an imidazolium-based ionic liquid by molecular dynamics simulation

Abstract: The effects of repulsive interaction on the electric double layer (EDL) and differential capacitance (Cd) of an ionic liquid (IL) 1-butyl-3-methyl-imidazolium hexafluorophosphate (BMIM(+)/PF6(-)) on the graphite electrode were studied by molecular dynamics (MD) simulations. The strength of repulsive interaction was studied by manually tuning the parameter lambda (λ) with λ = 1.00 for normal Lennard-Jones interaction and smaller λ for stronger repulsion between IL and the electrode. When λ changes from 1.00 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 36 publications
4
14
0
Order By: Relevance
“…Many researchers are working to understand the interfacial features with molecular dynamics (MD) simulation. Many researchers found that imidazolium-based ILs had similar layer structures adjacent to the electrode interface which is consistent with experimental findings. They concluded that there are multilayer structures (10–30 Å) near electrodes. In addition, imidazolium rings are almost parallel to electrodes at the first adsorbed layer and have a random orientation in bulk.…”
Section: Introductionsupporting
confidence: 69%
“…Many researchers are working to understand the interfacial features with molecular dynamics (MD) simulation. Many researchers found that imidazolium-based ILs had similar layer structures adjacent to the electrode interface which is consistent with experimental findings. They concluded that there are multilayer structures (10–30 Å) near electrodes. In addition, imidazolium rings are almost parallel to electrodes at the first adsorbed layer and have a random orientation in bulk.…”
Section: Introductionsupporting
confidence: 69%
“…At higher voltages (Δ U > 6–7 V), however, the simulations of realistic RTILs such as [C 4 mim]­[PF 6 ] , and [pyr 13 ]­[FSI] showed a decay of DC scaling as ∝1/| U electrode | 1/2 , which is in perfect agreement with the asymptotic and system independent behavior predicted by the Kornyshev model . Many molecular simulations of conventional RTILs near flat electrode surfaces have predicted an absolute value of DC between 4 and 5.5 μF/cm 2 . ,,,, Similar values of capacitances, of around 5 μF/cm 2 , were predicted for solutions of RTILs in acetonitrile solvents and for Li-salts dissolved in carbonates. , These theoretical predictions for DCs are in good quantitative agreement with the experimental works by Drüschler et al, Alam et al, Cannes et al, and Costa et al , …”
supporting
confidence: 54%
“…Heterogeneous microstructures and dynamical quantities of ILs in the IL–graphene interfacial region are essentially correlated with their functionalities in applications, such as in electrochemical devices ,, and in lubrication. Yan and co-workers performed intensive atomistic simulations studying effects of anion structures, , temperatures, and specific interactions of ions with graphene , on EDL structures and capacitive functionalities of imidazolium ILs confined between graphene electrodes. On one side, specific adsorption of imidazolium cations on the graphene electrode causes a positive potential of zero charge (PZC) on a positively charged electrode and a depression of capacitance at positive polarization .…”
Section: Ionic Liquids In Interfacial Regionsmentioning
confidence: 99%